Synthesis, structure and properties of a nickel coordination polymer with 3D supramolecular framework. Issue 3 (4th March 2017) - Li, Fu-An; Yang, Wei-Chun; Li, Song-Tian; Miao, Xu
ABSTRACT: One nickel coordination polymer with 3D supramolecular framework based on 5-(imidazol-1-ylmethyl)isophthalic acid (H2 L) as a main ligand and 1, 2-bis(4-pyridyl) ethene (bpe) as a N-containing ancillary ligand, {[NiL(bpe)(H2 O)]·(H2 O)3 } n (1 ), has been obtained by hydrothermal synthesis and characterized by powder X-ray diffraction (PXRD), UV/vis, IR, elemental analysis, thermal gravimetric analysis (TGA) and single-crystal XRD. It crystallizes in the monoclinic, space group P 21 / c . In1, L 2− anions connect Ni(II) ions forming 2D layers (Ni3 L3 )n and then adjacent layers are further associated together by π···π interaction leading to double layers, which are formed by the neighboring imidazolyl group. Meanwhile, hydrogen-bonding interactions between layers extend these double layers into 3D supramolecular network.